In Vitro Evaluation Of Antibacterial Activity Of Heartwood Extract Of Acacia Catechu Willd - LAKSHMI T; GEETHA R.V; ANITHA ROY (International Journal of Pharma and Bio Sciences, 2011)
The objective of the present study was to assess the anti bacterial activity of Acacia catechu willd (AC). AC is a moderate sized deciduous tree growing in tropical countries commonly called “Karungali” in Tamil. It is a potent medicinal plant in the traditional Indian medicinal systems. Aqueous and ethanolic extract of Heartwood of Acacia catechu is tested for antibacterial activity against Staphylococcus aureus, Bacillus subtilis, E.coli, Pseudomonas aeruginosa, Klebsiella pneumoniae. Disc diffusion technique was followed for screening anti bacterial activity. The discs were loaded with 50µl of aqueous and ethanolic extracts at different concentrations. Positive controls used were Amoxycillin (30 µg/disc) and Ciprofloxacin (5 µg/disc). After incubation at 37ºc over night, the zone of Inhibition was measured. Ethanolic extract showed significant activity than Aqueous extract against the micro organism compared to standard.